Livelihoods of Otter fishers` in the South-Western zone of Bangladesh - Siddique, Abu Bokkar; Surovi, Tasnim Jahan (Research in Agriculture Livestock and Fisheries, 2021)
Fishing with otters is an ancient fishing technique in Bangladesh, exists only in the south-western part of the country with smooth-coated Otter (Lutrogale perspicillata). The present study was carried out to portray this unique fishing technique and to investigate otter fishers` livelihood status in Narail District. Fishing with otters is carried out at night in the Chitra and the Nabaganga rivers, involving at least four people, a boat, a net, 2-3 adult tamed otters and 1-2 immature trainee otters. The socio-economic conditions and livelihood status of the otter fishers` were found as not-satisfactory level whereas about 75% of total 36 fishermen were termed as very poor and they don`t have their own boat and nets for fishing. All of the surveyed fishers belong to the Hindu religion and less access to education, pure drinking water, and a healthy sanitation system. Due to scanty income, and resultant low-living standard, 14 otter fishers were found changed their ancient profession. Therefore, direct interventions are essential to support improved and sustainable socio-economic condition of the otter fishing community. Res. Agric., Livest. Fish.8(2): 249-257, August 2021